2013
DOI: 10.1111/nph.12188
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the novel mycorrhiza‐specific phosphate transporter AsPT1 and PHT1 family from Astragalus sinicus during the arbuscular mycorrhizal symbiosis

Abstract: SummaryArbuscular mycorrhizas contribute significantly to inorganic phosphate (Pi) uptake in plants. Gene networks involved in the regulation and function of the Pht1 family transporters in legume species during AM symbiosis are not fully understood.In order to characterize the six distinct members of Pht1 transporters in mycorrhizal Astragalus sinicus, we combined cellular localization, heterologous functional expression in yeast with expression/subcellular localization studies and reverse genetics approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 58 publications
12
115
1
3
Order By: Relevance
“…The dynamics of arbuscule level in roots was confirmed by the expression of AM-specific Pi transporter gene AsPT4, which is particularly expressed in arbusculated cells and therefore an indicator of the function of AM symbiosis ( Xie et al, 2013). It was found that the expression profiles of GigmPT were similar to that of AsPT4 over time ( Figure 3B).…”
Section: Gigmpt Is Expressed Both In the Intraradical And Extraradicamentioning
confidence: 55%
See 3 more Smart Citations
“…The dynamics of arbuscule level in roots was confirmed by the expression of AM-specific Pi transporter gene AsPT4, which is particularly expressed in arbusculated cells and therefore an indicator of the function of AM symbiosis ( Xie et al, 2013). It was found that the expression profiles of GigmPT were similar to that of AsPT4 over time ( Figure 3B).…”
Section: Gigmpt Is Expressed Both In the Intraradical And Extraradicamentioning
confidence: 55%
“…The subcellular localization of GigmPT in yeast was examined with a C-terminal fusion of GigmPT to GFP in the yeast strain as described by Xie et al (2013). The image capture was performed using a fluorescence microscope (Olympus BX51, Japan).…”
Section: Localization Of Gigmpt In Yeast Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al (2015) found that drought stress upregulated the level of R. intraradices and soybean mitogen-activated protein kinase (MAPK) transcripts in mycorrhizal soybean roots, indicating the possibility of a molecular dialogue between AM fungus and host plant and suggesting that they might cooperate to improve soybean’s resistance to drought stress. Concurrently, in terms of nutrient absorption, some studies investigated the mycorrhiza-regulated phosphate transporters in host plants Astragalus sinicus (Xie et al 2013), Oryza sativa (Sun et al 2012), P. tabulaeformis (Zheng et al 2016a), pepper and tobacco (Chen et al 2007), and reciprocal transportation of carbon and phosphorus amongst plants ( Zea mays and Medicago sativa ), Rhizophagus irregularis and phosphate-solubilising bacterium (Zhang et al 2016; Wang et al 2016a). Wang et al (2014) demonstrated that H + -ATPase played a key role in energising the periarbuscular membrane, thereby facilitating nutrient exchange in arbusculated rice and Medicago truncatula cells.…”
Section: Molecular Biology Of Mycorrhizal Fungimentioning
confidence: 99%